Improving purity of bio-based crotonic acid - Farid, Nur Falia Shazana Manja (2015)
Crotonic acid is an unsaturated carboxylic acid derived from petroleum resource which is currently used as components of hair styling products, insecticides, softening agent for synthetic rubber and plasticizer. At present, commercial crotonic acid is chemically synthesized from non-renewable resource through multi-step chemical synthesis. Recently, bio-based crotonic acid production has been introduced through pyrolysis of bacterial polyhydroxybutyrate (P(3HB)) inclusions, however the purity of the crotonic acid produced was low (54%). Therefore, this study was done aimed at improving the purity of bio-based crotonic acid. In this study, P(3HB) was produced by Cupriavidus necator KCTC 2649 utilizing oil palm frond (OPF) juice. P(3HB) inclusion produced had the purity of 75%. Effect of mild alkali pretreatment on P(3HB) purity and subsequently crotonic acid purity was tested by using 0.05M NaOH. It was found that crotonic acid produced from NaOH-treated P(3HB) had purity of 92 %. Results from this study showed that NaOH treatment not only caused the improvement in P(3HB) purity which consequently caused the increment in crotonic acid purity, but it also caused the molar mass of the P(3HB) to reduce to form lower molar mass P(3HB) with crotonyl chain-end. This condition accelerated -chain scission of P(3HB) into crotonic acid. Additionally, NaOH treatment caused the presence of Na metal cation which initiated -deprotonation of P(3HB), followed by the formation of unsaturated crotonic acid. It was believed that the purity of the crotonic acid produced can be improved by introducing metal compounds during pyrolysis of NaOH-treated P(3HB) in order to selectively degrade the P(3HB) into crotonic acid. Results revealed that the type of metal cation used caused a marked different in crotonic acid formation, whereby MgCl2 gave the highest crotonic acid purity at 92 %, followed by NaCl and CaCl2 at 90 and 88 %, respectively. This observation was contributed by ion size of the cation; the smaller the size of the cation, the higher the crotonic acid produced. On the other hand, the effect of anion was not pronounced as all the anions of Mg compounds used i.e. Cl-,OH- and O2- gave almost similar crotonic acid purity at 98-99%. Overall, it can be concluded that the purity of bio-based crotonic acid was tremendously improved with mild alkaline pre-treatment and addition of alkaline earth compounds. The results from this study contribute to the novel and renewable production of high purity bio-based crotonic acid.